Asymmetric effects of policy uncertainty on the demand for money in the United States - Mohsen Bahmani-Oskooee; Majid Maki Nayeri (Journal of Risk and Financial Management, 2019)
A comprehensive measure of economic uncertainty, known as "Policy Uncertainty", which was constructed by the Economic Policy Uncertainty Group by searching popular newspapers for uncertain terms associated with economic factors and its impact on macro variables, is gaining momentum. Although some researchers have assessed its impact on the demand for money in a few countries, we considered the U.S.A. demand for money one more time and showed that when a linear money demand was estimated, policy uncertainty had no long-run effects. However, when a nonlinear model was estimated, the results showed that while increased policy uncertainty induces the public to hold less money in the long run, decreased uncertainty has no long-run effects, a clear sign of asymmetric response.
Keywords: E41; 330; policy uncertainty; money demand; the U.S.A.; asymmetry; nonlinear ARDL